Behaviour of several chokeberry cultivars (Aronia melanocarpa) at the in vitro micropropagation - Zs. Jakab I; L.D. Vlașin; A.M. Chiorean (Romanian Journal of Horticulture, 2022)
Successful micropropagation of black chokeberry (Aronia melanocarpa) cultivars ‘Nero’, ‘Melrom’ and ‘Galicjanka’ was realized using young shoots with the aim of an optimized hormones concentration for initiation, multiplication and rooting phases. Good potential of initiation was observed at ‘Nero’ and ‘Galicjanka’ cultivars, respectively of shoots regeneration at ‘Galicjanka’ and ‘Melrom’ cultivars. Results showed that the use of antioxidant solutions is crucially in the initiation phase in order to prevent explants oxidation. Good initiation rates were obtained at ‘Nero’ (57 %) and ‘Galicjanka’ (57%) cultivars, while for ‘Melrom’ the rate was only 33% by using a hormonal balance of 0.7 mg/L BAP and a reduced level of 0.3 mg/L GA3. The in vitro shoots multiplication rate was relatively stable during the first subcultures. Best micropropagation rates were obtained at ‘Galicjanka’ and ‘Melrom’ cultivars followed by ‘Nero’ cultivar, using a 0.7 mg/L BAP and 0.5 mg/L GA3. The study showed also that, rooting process is enhanced when the culture medium contains activated charcoal (1.2 g/L) and a lower IBA concentration (0.5 mg/L) compared with the application of higher auxin concentration of the same hormone (1.0 mg/L). Activated charcoal seems to promote a good rooting process, thus being very important in the rooting phase. Researches revealed that the genotype influences the capacity of inoculums regeneration, the multiplication capacity and the rooting ability.